CONSTRUCTING VICTIMS AND VILLAINS: IDEOLOGICAL POLARIZATION IN TRUMP’S SPEECH ON CHARLIE KIRK - Kristianto, Ignatius Indra (LATTE: A Journal of Language, Culture, and Technology ISSN 3063-0754, 2025)
Political speeches constitute collective perception through event framing, identity construction, and emotional mobilization and hence are of the utmost importance for understanding the way language supports power and ideology. Although the rhetoric of Donald Trump has been studied in terms of nationalism, populist moral binaries, and emotional polarization, his memorial speeches have not received attention so far as ideological tools. Drawing on the methodological apparatus of Critical Discourse Analysis, the current study integrates Fairclough’s three-dimensional model with Van Dijk’s ideological square. It analyzes how “victims” and “villains” are discursively constructed and what ideological functions these constructions serve in Trump's speech after the assassination of the conservative activist Charlie Kirk. The study analyzes the official transcript of the speech. The results indicate that Trump constructs the victim, Kirk, with the help of sacralized and heroic frames that scale up individual loss into national trauma, while simultaneously extending the category of victims to “all Americans.” On the other side, villains are constructed by dehumanization and causal attribution: blame is attributed to the radical left, media, and related institutions, widening the circle of blame. Such representations realize important ideological functions: first, they reinforce polarization by means of strong moral binaries; second, they turn personal tragedy into political mobilization. Furthermore, positioning Trump as a protector figure creates emotional resonance, thereby firmly strengthening audience loyalty. This paper shows that the speech works not only as a form of eulogy but also as a persuasive strategy in solidifying identity boundaries and political support. The findings add to the scholarship of political communication and CDA, having implications for teaching persuasive discourse in business and organizational contexts.